What really matters for successful research environments? A realist synthesis. Issue 9 (24th July 2018) - Ajjawi, Rola; Crampton, Paul E S; Rees, Charlotte E
Abstract : Context: Research environments, or cultures, are thought to be the most influential predictors of research productivity. Although several narrative and systematic reviews have begun to identify the characteristics of research‐favourable environments, these reviews have ignored the contextual complexities and multiplicity of environmental characteristics. Objectives: The current synthesis adopts a realist approach to explore what interventions work for whom and under what circumstances. Methods: We conducted a realist synthesis of the international literature in medical education, education and medicine from 1992 to 2016, following five stages: (i) clarifying the scope; (ii) searching for evidence; (iii) assessing quality; (iv) extracting data, and (v) synthesising data. Results: We identified numerous interventions relating to research strategy, people, income, infrastructure and facilities (IIF), and collaboration. These interventions resulted in positive or negative outcomes depending on the context and mechanisms fired. We identified diverse contexts at the individual and institutional levels, but found that disciplinary contexts were less influential. There were a multiplicity of positive and negative mechanisms, along with three cross‐cutting mechanisms that regularly intersected: time; identity, and relationships. Outcomes varied widely and included both positive and negative outcomes across subjective (e.g. researcher identity) and objective (e.g. research quantity and quality) domains. Conclusions: The interplay among mechanisms and contexts is central to understanding the outcomes of specific interventions, bringing novel insights to the literature. Researchers, research leaders and research organisations should prioritise the protection of time for research, enculturate researcher identities, and develop collaborative relationships to better foster successful research environments. Future research should further explore the interplay among time, identity and relationships. Abstract : This realist review shows when and why interventions related to research strategy; people; income, infrastructure and facilities; and collaboration result in positive or negative research environments. Findings indicate that protected time, researcher identities and collaborative relationships are important for fostering successful research environments.